Adventures of the Little Wooden Horse - "Williams, Ursula Moray" (Puffin Books: London, 1994)
The little wooden horse is Uncle Peder's finest creation, but no one wants to buy him, so he stays with his master and the two become great friends. When the toymaker grows poor and ill, the brave little horse sets out to sell himself.
Keywords: Toys Fiction